Putting television in its place: the domestication of the television set in Britain 1936-1976 - Rees, Emily F (2019)
This thesis examines how the television set was domesticated in Britain, from the beginning of the television service in 1936, to the introduction of colour in the 1970s. The thesis centres on the issue of television’s domestic consumption, through the consideration of television as a physical object that resides in the home, not just as a disseminator of information into the home.